2008
DOI: 10.4238/vol7-4gmr498
|View full text |Cite
|
Sign up to set email alerts
|

Can established cultured papilloma cells harbor bovine papillomavirus?

Abstract: ABSTRACT. Papillomaviruses have been reported to be very difficult to grow in cell culture. Also, there are no descriptions of cell cultures from lesions of bovine cutaneous papillomatosis, with identification of different bovine papilloma virus (BPV) DNA sedifferent bovine papilloma virus (BPV) DNA sequences. In the present report, we describe primary cell cultures from samples of cutaneous lesions (warts). We investigated the simultaneous presence of different BPV DNA sequences, comparing the original lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
1
12
0
5
Order By: Relevance
“…The identification of several genotypes of papilloma virus (BPV-1, BPV-2, and BPV-13) indicated mixed infections, which were widespread in animals with cutane- ous warts in diverse portions of their body. These results are in agreement with those of Campos et al [43], who also found that cattle, as well as buffalo, had mixed infections of BPV-1, BPV-2, and BPV-13 [44]. We did not find any significant differences in lesions, either grossly or histologically, between samples in relation to specific genotypes, meaning that there may need to be specific studies in the future focusing on these parameters.…”
Section: Discussionsupporting
confidence: 82%
“…The identification of several genotypes of papilloma virus (BPV-1, BPV-2, and BPV-13) indicated mixed infections, which were widespread in animals with cutane- ous warts in diverse portions of their body. These results are in agreement with those of Campos et al [43], who also found that cattle, as well as buffalo, had mixed infections of BPV-1, BPV-2, and BPV-13 [44]. We did not find any significant differences in lesions, either grossly or histologically, between samples in relation to specific genotypes, meaning that there may need to be specific studies in the future focusing on these parameters.…”
Section: Discussionsupporting
confidence: 82%
“…, 2015), placenta (Roperto et al,. 2012) and primary cell cultures (Campos et al , 2008; Campos et al , 2013). Similar results have also been described for HPV (Chiou et al , 2003; Foresta et al , 2013; Pessoa, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the in vitro systems are additional and useful model to study the biology of BPV, as discussed by Campos et al [18]. The analysis of cell cycle showed a high percentage of BPVinfected cell in S and/or G2-M phases (figure 2), demonstrating the hyperproliferative action of BPV in vitro.…”
Section: Discussionmentioning
confidence: 52%